The Piedra Chamana Fossil Forest: A scientific resource of global importance - Woodcock, Deborah (2020)
The Piedra Chamana Fossil Forest, near the village of Sexi in central Cajamarca, records the vegetation of the South American tropics 39 million years ago, early in the New World tropical forests history and before the rise of the present-day Andes. In this fossil forest, notable discoveries have included the mangrove genus Avicennia, a genus of emergent forest trees (Cynometra), and the second dipterocarp known from the New World. The significance of the fossils rests on the unique circumstances of preservation, the detailed reconstruction of the forest and environment that is possible based on the plant fossils and ancient soils, and the importance of this record for the study of climate change. Sites like the fossil forest are particularly vulnerable to disturbance and loss of the fossil resources. Ongoing monitoring shows that human activities and erosion are having serious effects and, conservation measures are urgently needed. The importance of the fossils for science, the beauty of this area of the Andes, and the potential of the site for education and tourism justify recognition of the fossil forest at an international level. The lowland tropical forest represented by the fossils is very different from the diverse broad-leaf sclerophyllous forest or woodland now growing in the area. Soil loss and erosion of the soft, porous volcanic substrate when the vegetation cover is disturbed poses a threat to both the native biota and the fossils. The conservation measures needed at the fossil site would have multiple benefits for the ecology of the region.